Survei Minat Belajar Siswa SD Kelas VI Se Desa Blendung Dalam Mengikuti Pembelajaran PJOK Secara Daring - Wisnu Panji Kusuma; Ibnu Fatkhu Royana; Fajar Ari Widiyatmoko (Journal of Physical Activity and Sports (JPAS), 2023)
The background of the problem in this study is online learning which affects students 'interest in learning Physical Education during the Covid-19 pandemic, therefore there is a need for a description of the student's interest in learning Physical Education during online or School From Home (SFH). The purpose of this study was to determine the description and influence of interest in learning in taking physical education lessons using the online system for students of Class VI Elementary School in Blendung Village. The research method used is descriptive quantitative research using a direct survey method. . The samples of this research were students of SDN 1, SDN 2, and SDN 3 Blendung using the total sampling technique. The research results of the physical education learning interest survey can be seen from a questionnaire with 23 statement items and 82 respondents have the highest score of 79 and the lowest score of 53. It has a range of 26 then processed using Microsoft Excel and obtained an average of 63.36 minimum value of 51, a maximum value of 79, a standard deviation of 4.78, and a variant of 22.45, a tendency of 50% or 42 students with very high, 37% or 30 students high, 9% or 7 students low, 4% or 3 students very low. . The conclusion of this study is the tendency of student interest in learning there are 42 students or 50% have a very high tendency, 30 students, or 37% have a high tendency, 7 students, or 9% have a low tendency, 3 students, or 4% have a very low tendency. So that it can be seen that students' interest in learning Physical Education online is said to be in the very high category.